Sarcopenia and sarcopenic obesity are significantly associated with poorer overall survival in patients with pancreatic cancer: Systematic review and meta-analysis. (November 2018) - Mintziras, Ioannis; Miligkos, Michael; Wächter, Sabine; Manoharan, Jerena; Maurer, Elisabeth; Bartsch, Detlef Klaus
Abstract: Backround: The role of sarcopenia and sarcopenic obesity in patients with pancreatic ductal adenocarcinoma(PDAC) remains controversial. Material and Methods: Medline and Web of Science were searched for studies reporting survival in sarcopenic and/or sarcopenic obese patients with pancreatic cancer. Primary outcome was mortality in patients with sarcopenia and/or sarcopenic obesity versus non-sarcopenic and/or non-sarcopenic obese patients. Secondary outcome was the incidence of major postoperative complications. Results: Eleven studies comprising 2.297 patients were considered suitable for inclusion. Overall 959 of 2.111(45.4%) patients were defined as sarcopenic and 163 of 1.254(13%) as sarcopenic obese. Patients' age was above 60 years(range 63-69) with a male proportion ranging from 50.8% to 68.0%. Of 2.297 patients, 958(41.7%) underwent palliative treatment, 1.339(58.3%) curative resections. Follow-up ranged from 11 to 57.7 months. Median overall survival ranged from 4.3 to 12 months in palliative patients and 17.4 to 25.8 months after curative resection. Overall proportions of sarcopenic patients varied from 21.3% to 65.3%. Sarcopenia was significantly associated with poorer overall survival(HR 1.49; 95%CI 1.27-1.74, p<0.001). Sarcopenic obesity was reported in 0.6% to 25.0% of patients, and was also significantly associated with poorer overall survival(HR 2.01; 95%CI 1.55-2.61, p<0.001). The incidence of major complications ranged from 8.6% to 33.9%. Rates of clinically relevant(grade B/C) postoperative pancreatic fistulas varied from 8.3% to 17.8%. Sarcopenic obesity was an independent predictor of major postoperative complications in one study, in another study sarcopenia was significantly associated with clinically relevant pancreatic fistulas. Conclusions: Sarcopenia and sarcopenic obesity are significantly associated with poorer overall survival in patients with PDAC. Highlights: This meta-analysis assesses the role of sarcopenia and sarcopenic obesity in patients with pancreatic ductal adenocarcinoma(PDAC). Primary outcome was mortality, secondary outcome was the incidence of major postoperative complications. Sarcopenia was significantly associated with poorer overall survival(HR 1.48; 95%CI 1.26-1.74, p<0.001). Sarcopenic obesity was also significantly associated with poorer overall survival(HR 2.01; 95%CI 1.55-2.61, p<0.001). Sarcopenia and sarcopenic obesity are significantly associated with poorer overall survival in patients with PDAC.